Effect of arsenic in endochondral ossification of experimental animals - Aybar Odstrcil, Ana del Carmen (2010)
Arsenic (As) toxicity is a global health problem affecting millions of people, the most toxic forms being Arsenites [As(III)] and Arsenates [As(V)]. Arsenic intoxication can occur through different exposure routes. The aim of the present work was to determine the effect of As on endochondral ossification and bone remodeling in experimental animals, by means of biochemical, histologic, and histomorphometric determinations.Sixteen male Wistar rats, 100g body weight (b.w.), were divided into two groups: experimental group (n=8), treated with 10mg/l of NaAsO2 in their drinking water, receiving 0.21mg/kgb.w./day during 45 days; and control group (n=8) remained untreated. On day 45, blood samples were obtained by cardiac puncture to perform hematologic blood counts and biochemical determination. The animals were killed, the tibiae, femurs, kidneys and livers were resected, fixed in formalin and processed histologically. Tibia and femur sections were obtained and stained with H&E. The following histomorphometric parameters were determined on tibia and femur sections: bone volume (BV/TV), thickness of growth plate cartilage (GPC.Th) and thickness of hypertrophic zone (HpZ.Th).Biochemical determinations showed that experimental animals exhibited neutrophilia and a decrease in lymphocytes and monocytes. As levels were below 1 μg/dl in both groups. The femur sections of the experimental group showed (1) a statistically significant increase in total growth cartilage plate thickness (. p<0.05) at the expense of the hypertrophic zone (. p<0.05); (2) subchondral trabecular bone sealed to the growth plate with a non-significant increase in primary spongiosa bone volume. These results suggest that As alters endochondral ossification.